Subjective Impairments in Olfaction and Cognition Predict Dissociated Behavioral Outcomes. (24th August 2022) - Cedres, Nira; Aejmelaeus-Lindström, Andrea; Ekström, Ingrid; Nordin, Steven; Li, Xin; Persson, Jonas; Olofsson, Jonas K
Abstract: Background: Self-rated subjective cognitive decline (SCD) and subjective olfactory impairment (SOI) are associated with objective cognitive decline and dementia. However, their relationship and co-occurrence is unknown. We aimed to (a) describe the occurrence of SOI, SCD and their overlap in the general population; (b) compare SOI and SCD in terms of longitudinal associations with corresponding objective olfactory and cognitive measures; and (c) describe how SOI and SCD may lead to distinct sensory and cognitive outcomes. Methods: Cognitively unimpaired individuals from the third wave of the Swedish population-based Betula study ( n  = 784, aged 35–90 years; 51% females) were split into self-rated SOI, SCD, overlapping SCD + SOI, and controls. Between-subject and within-subject repeated-measures MANCOVA were used to compare the groups regarding odor identification, cognition, age, sex, and education. Spearman correlation was used to assess the different patterns of association between olfaction and cognition across groups. Results: SOI was present in 21.1%, whereas SCD was present in 9.9% of participants. According to a chi-square analysis, the SCD + SOI overlap (2.7%) is on a level that could be expected if the phenomena were independent. Odor identification in SOI showed decline at the 10-year follow-up ( n  = 284) and was positively associated with cognition. The SOI and SCD groups showed distinct cognitive-olfactory profiles at follow-up. Conclusions: SOI occur independently of SCD in the population, and these risk factors are associated with different cognitive and olfactory outcomes. The biological causes underlying SOI and SCD, as well as the risk for future cognitive impairment, need further investigation.